Analisisi Kekakuan Pelat Baja Galvanil Ketebalan 0,6 MM Akibat Pembentukan Dengan Metode Bead Rolled - M Fadillah, Febian; Erwanto, Erwanto (Manutech : Jurnal Teknologi Manufaktur, 2024)
The cold forming process for thin plates is widely used and essential in the manufacturing industry, particularly in the automotive sector. One such cold-forming method is the bead roll process, commonly referred to as "Bead Roll." This process is popular due to its low cost and its ability to improve vibration resistance effectively. The "Bead Roller" machine is used to create grooves or profiles on sheet metal plates. Based on experimental analysis of the collected data, the plate with the best damping capability was found to be the one processed using a roll width of 10 mm and a rolling depth of 3 mm. This research is expected to expand knowledge about plates as an innovative new form and serve as a reference for future research and development